The utilization of a fiberglass mesh–reinforced foamcrete jacketing system to enhance mechanical properties - Mat Serudin, Anisah; Mydin, Md Azree Othuman; Mohd Nawi, Mohd Nasrun; Deraman, Rafikullah; Sari, Marti Widya; Abu Hashim, Mohammad Firdaus (MDPI, 2022)
Foamcrete is fabricated by combining mortar slurry and constant foam. Owing to the existence of air entrained in its cementitious matrix, foamcrete is tremendously brittle compared to normal-strength concrete. The addition of synthetic and natural plant fibers demonstrates an enhancement to foamcrete’s mechanical performance yet exerts a harmful effect on long-term performance. Depreciation of natural plant fibers and corrosion of synthetic fibers impact the lifespan and durability properties of foamcrete. Hence, this study aims to investigate the mechanical properties and mode of failures of foamcrete reinforced with fiberglass mesh (FM). The parameters assessed were the compression, flexural, and splitting tensile strengths of 1100 kg/m3 density foamcrete confined with various layers of 145 g/m2 of FM. The optimal foamcrete mechanical properties enhancement was attained with three-layer jacketing. Notable augmentations of 108% in the compressive strength, 254% in flexural strength, and 349% in splitting tensile strength were achieved in comparison to the control specimens at day 28. The control foamcrete samples under compressive, flexural, and tensile loads encountered brittle failure in comparison to the confined foamcrete. The mode of failure under the tensile load indicates that only a slight crack occurred at the upper side and a perpendicular mark at the lateral section of the foamcrete with one to three layers of FM jacketing. Thus, the jacketing system of foamcrete with FM enhances the behavior and load carrying capacity of foamcrete to the extent of preventing the propagation of cracks